A clinical case of synchronous endometrial and ovarian cancer associated with pregnancy - A. L. Chernyshova; L. A. Kolomiets; Yu. M. Trushchuk; O. S. Dil; A. A. Chernyakov; S. E. Krasilnikov; V. A. Antipov; A. E. Chernyshov (Опухоли женской репродуктивной системы)
According to various literature sources, in the general population of women with synchronous endometrial cancer and ovarian cancer is quite rare. We have not found a single foreign or domestic literary source describing clinical cases of primary multiple malignant tumors: synchronous endometrial cancer and ovarian cancer associated with pregnancy.We present an interesting clinical example that clearly demonstrates the possibility of successful treatment of this variant of primary multiple malignant tumors – synchronous endometrial cancer and ovarian cancer associated with pregnancy. The features of the course of the disease, the features and difficulties of treatment of this pathology are shown. And also the high efficiency of the treatment was shown according to the morphological study with an assessment of the drug pathomorphosis according to Lavnikova.A case of successful combined treatment is presented, taking into account the combined pathology. According to the received data, it is possible to conclude. The management of pregnant women and the treatment of cancer should be carried out in specialized centers with experience in the treatment of oncological diseases associated with pregnancy.